Gingival immunologic defense index: a new indicator for evaluating dental plaque infection risk in allergic children - Seno Pradopo; Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
There is a possible relationship between dental plaque and children allergic diseases. According to literatures, gingivitis suffered mostly by allergic children than control. Case reports also revealed that dental plaque control therapy was able to reduce, even eliminate rhinosinusitis and asthmatic symptoms without additional medications. However, the exact method for confirming the gingivitis-related allergy is still uncertain. Allergic diseases have multifactorial etiologies and dental plaque had been proposed as a new trigger of allergic symptoms. Nevertheless, since not every child with gingivitis suffered from allergy or vice versa, this uncertain phenomenon may lead to patients or other clinician disbelief. The objective of the present study was to propose a new method, which involving the Gingival immunologic defense index (GIDI) to evaluate the susceptibility to allergic diseases. GIDI is an index that had been developed earlier for evaluating gingival immunologic defense with respect to immunoglobulin A (IgA) levels. This index based on the simple count of the inflamed gingival surfaces of a child plus the measurement of salivary IgA content. It provides clinicians with important information about the immunologic defense potential of each subject. Interestingly, most allergic children also had inherited IgA deficiency, thus this concept is likely. Based on literatures, GIDI could be a potential index for evaluating the risk of allergic diseases through gingival health assessment. However, prior investigation to the value of Indonesian GIDI index which related to allergy should be conducted.